Some methods of fish capture in Palawan waters and Laguna de Bay - Garcia, Jacinto Bunyi (Miagao, Iloilo College of Fisheries, University of the Philippines, 1954)
Our fishing industry is the second most important industry in our country today without fishing; the protein supply of the people will hardly be met. Fortunately, however the Philippine waters are rich with fish and fishery products. The government has now waged all efforts to protest the industry. They enabled laws designed to conserve our fishery resources and also appealed to all free-loving citizens to help and cooperate with the duly constituted authorities in the enforcement of this laws. This paper present the description of some methods of catching fishes in Palawan waters and Laguna de Bay. It also includes the organizations as well as the operation and management of the corresponding fishing outfits. These fishing methods were observed during my apprenticeship in the months of May to October, some of them may slightly differ from the types of methods used by fishermen from other fishes are there, having the striking similarity if not altogether the same.
Keywords: Fish capture